Early performers and performance in the northeast of England - Wyatt, Diana; McKinnell, John (Leeds : Arc Humanities Press, 2021)
This collection explores the evidence for a wide variety of performance traditions up to 1642 in the northeast region of England which was among those most remote from London. While noble and religious houses in the northeast often patronized visiting performers and might be aware of developments in the capital, the region also had lively performance traditions of its own, on every level of society, from the wedding revels, sporting activities, and household fools of major noble families, through civic plays and processions, to the customary annual performances of hunters and ploughmen. The bo.
Frontmatter -- CONTENTS -- List of Illustrations -- Acknowledgements -- Introduction -- Contributors -- Chapter 1. Comic Performance in the Tudor and Stuart Percy Households -- Chapter 2. Wedding Revels at the Earl of Northumberland's Household -- Chapter 3. Weddings and Wives in some West Riding Performance Records -- Chapter 4. Travelling Players on the North Yorkshire Moors -- Chapter 5. Travelling Players in the East Riding of Yorkshire -- Chapter 6. Northern Catholics, Equestrian Sports, and the Gunpowder Plot -- Chapter 7. Wool, Cloth, and Economic Movement: Journeying with the York and Towneley Shepherds -- Chapter 8. Visiting Players in the Durham Records: An Exotic Monster, a French Magician, and Scottish Ministralli -- Chapter 9. Rural and Urban Folk Ceremonies in County Durham -- Chapter 10. Rush-bearings of Yorkshire West Riding -- Chapter 11. Boy Bishops in Medieval Durham -- Chapter 12. Regional Performance as Intangible Cultural Heritage -- Bibliography -- Index
Online resource; title from digital title page (viewed on May 11, 2021).
JSTOR
Keywords: Entertainers -- England, North East -- History -- To 1500.; Theater -- England, North East -- History -- To 1500.; English drama -- To 1500 -- History and criticism; Théâtre -- Angleterre (Nord-Est) -- Histoire -- Jusqu'à 1500.; Théâtre anglais -- Jusqu'à 1500 -- Histoire et critique; DRAMA -- Medieval; English drama; Entertainers; Theater; England -- England, North East; To 1500; Criticism, interpretation, etc; History